GOALS AND OBJECTIVES TRAINING OF CYCLING SPORTS - Umarov, Sarvar Mirzagitovich (Educational Research in Universal Sciences, 2023)
In this scientific article, a study was conducted to identify the most effective interactive teaching methods in the course of training sessions on the subject "Theory and methodology of cycling" with students of the Uzbek State University of Physical Culture and Sports. Pedagogical recommendations are given on the use of active and interactive forms of classes for the formation and development of professional and pedagogical abilities of students.